2020
DOI: 10.3897/zookeys.923.39665
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics reveals bamboo feeding adaptability in the giant panda (Ailuropoda melanoleuca)

Abstract: The giant panda (Ailuropoda melanoleuca) is one of the world’s most endangered mammals and remains threatened as a result of intense environmental and anthropogenic pressure. The transformation and specialization of the giant panda’s diet into a herbivorous diet have resulted in unique adaptabilities in many aspects of their biology, physiology and behavior. However, little is known about their adaptability at the molecular level. Through comparative analysis of the giant panda’s genome with those of nine othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Mannans are a major group of hemicellulose, and bamboo contains a large amount of hemicellulose, which is difficult for giant pandas to digest and utilize. The hypomethylation and higher expression of these genes related to polysaccharides or oligosaccharides hydrolysis facilitate the digestion and absorption of hemicellulose components in bamboo for giant pandas, which is also similar to the result of He et al (2020).…”
Section: Discussionmentioning
confidence: 57%
“…Mannans are a major group of hemicellulose, and bamboo contains a large amount of hemicellulose, which is difficult for giant pandas to digest and utilize. The hypomethylation and higher expression of these genes related to polysaccharides or oligosaccharides hydrolysis facilitate the digestion and absorption of hemicellulose components in bamboo for giant pandas, which is also similar to the result of He et al (2020).…”
Section: Discussionmentioning
confidence: 57%
“…The giant panda’s conversion to an herbivorous diet has produced unique adaptations in many aspects, for instance, pseudothumbs and a low energy metabolism rate, to accommodate to low-nutrient and low-energy consumption food [ 13 ]. The comparative genomic analysis revealed that the giant panda has similar genetic characteristics to carnivores in terms of olfaction [ 14 ]. The giant panda can use smell cues in urine and body odor to distinguish relatives from non-relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al argued that giant pandas maintain a low metabolic level through reductions in their activity levels, a shrinkage of major energy consuming organs, and a decline in thyroid hormone levels ( 2 ). Despite numerous studies on giant panda genomics ( 3 ), transcriptomics ( 4 , 5 ), and gut microbiome composition ( 6 ), it is unclear how pandas digest bamboo with a low metabolic rate. It is also uncertain how metabolic characteristics change with increasing age, particularly during the transitionary period from a milk-based diet in cubs to a bamboo-based diet in young pandas.…”
Section: Introductionmentioning
confidence: 99%